Idiomatic creativity: a pragmatic model for creative idiomatic uses in authentic English discourse - Vo, Thuc Anh (2011)
This thesis is a corpus-based investigation from a pragmatic perspective or the phenomenon of idiomatic creativity. The ultimate aim of the thesis is to provide comprehensive empirical evidence of the intertwining relationships between different factors of idiomatic creativity and the effects of such relationships on the reassessment of the determinants of idiomatic creativity in context-specific communicative events.